A comparison of hydrocarbon generation and expulsion in carbonate and argillaceous source rocks using semi-open pyrolysis experiments - Huang, Haiping; Li, Minghui; Yang, Chao; Zheng, Lunju (Marine and petroleum geology, 2023)
To investigate the hydrocarbon generation and expulsion efficiency from carbonate and argillaceous source rocks, a series of pyrolysis experiments were conducted on two representative samples with Type II kerogen in a semi-open simulation system. The shale sample was obtained from the Upper Cretaceous Second White Speckled Shale Formation, while the carbonate sample was collected from the Middle Devonian Brightholme Member of the Winnipegosis Formation, both from the Western Canada Sedimentary Basin. The results show that the carbonate has a higher hydrocarbon generation capacity than the shale. During the pyrolysis, the expelled hydrocarbons from the carbonate were about 100–200 mg/g TOC higher than the hydrogen index reduction, while the amount of expelled hydrocarbons from the shale was generally lower than the hydrogen index reduction. The peak oil generation from the carbonate occurred earlier than that from the shale, but the oil expulsion efficiency was lower. However, a larger quantity of unexpelled oil retained in the carbonate was conducive to later oil expulsion, more hydrocarbon gas generation, and slightly higher gas expulsion efficiency than for the shale. Although hydrocarbon gases generated from both sources share similar evolution trends with heating, the relative proportions of CO2 and methane differ significantly between the two lithologies, with much higher abundance of CO2 in shale pyrolysate. The carbon loss during maturation of the two source rocks is very similar during the oil generation window, but the carbon loss trend was reversed in shale after the onset of gas generation, due to the conversion of some bitumen to pyrobitumen. Conversely, carbon loss continued in the carbonate to a higher maturity stage. This difference can be attributed to the occurrence of different organic matter types in the carbonate, including dispersed organic matter, aggregated organic matter, crystal-enclosed organic matter, and inclusion-hosted organic matter. These various organic matter types contribute to continuous oil and gas expulsion over a much wider maturity range than shale. Although the two samples chosen for this study do not encompass the entire range of carbonate and shale formations, the established hydrocarbon generation and expulsion models and evaluation criteria for argillaceous source rocks may not be directly applicable to carbonates, particularly at high maturity stages. These valuable insights have significant implications for oil and gas exploration in diverse geological settings. The research highlights the tendency of carbonate source rocks to experience higher organic carbon loss during maturation compared to argillaceous rocks. This suggests that certain low-TOC, highly mature carbonate source rocks can potentially serve as effective hydrocarbon source rocks if successful oil expulsion occurs. These findings underscore the need to take into account the distinctive characteristics of carbonate source rocks when developing strategies for hydrocarbon exploration and production. •Semi-open simulation illustrates hydrocarbon generation and expulsion processes.•Carbonate reaches peak hydrocarbon generation earlier with about 40% more yield than shale.•Oil generation window in carbonate is wider but expulsion efficiency is lower than shale.•Organic carbon loss cease at peak oil generation in shale but continue to gas window in carbonate.•Models and assessment criteria established for shales are not applicable to carbonates.